Premarital Counseling Strategies of the Head of the Putri Betung Religious Affairs Office for Early-Marriage Prevention - Seri Minta; Zainal Arifin (Borneo International Journal of Islamic Studies, 2026)
Early marriage remains persistent in Putri Betung District, where educational limitations, economic pressures, local cultural norms, and insufficient family readiness influence marriage decisions. This study analyzes the premarital counseling strategies employed by the head of the Putri Betung Religious Affairs Office (KUA) to prevent early marriage. A qualitative case study was conducted at the Putri Betung Religious Affairs Office in February 2026 using observation, in-depth interviews, and document analysis. Three informants were purposively selected, consisting of one head of the KUA and two Islamic religious counselors. The data were analyzed using an interactive model comprising data condensation, data display, and conclusion drawing, while source and technique triangulation were employed to establish credibility. The findings, interpreted through an adapted Porter’s Five Forces framework, identified five interconnected strategies: community education and outreach, marriage guidance, persuasive engagement with religious and community leaders, cross-sectoral collaboration, and individual-awareness development. These strategies were implemented through scheduled and incidental counseling activities and supported by coordination with village authorities, schools, health services, and community figures. However, their implementation was constrained by the cultural acceptance of early marriage, economic vulnerability, low educational attainment, limited reproductive-health literacy, extensive geographical coverage, and inadequate institutional resources. The findings indicate that these strategies were reported to strengthen public understanding of marital readiness, although the study did not measure a statistical reduction in early-marriage cases. Therefore, the reported outcomes should be understood as perceived improvements in knowledge, awareness, and institutional coordination rather than conclusive evidence of a reduction in early marriage.